Removal of dissolved organic carbon from peat swamp runoff using groundnut shell - Chai, Hui Ping (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The study focuses on removal of dissolved organic carbon from peat swamp runoff by using groundnut shell. Three factors namely dosage, pH and contact time were optimized using three-level full factorial design. The adsorption efficiency was calculated based on the absorbance at 465 nm using a UV-Vis spectrometer. The highest percentage removal is 81.25 % under optimum condition (pH= 3; contact time= 60 min; dosage =5 g/l00mL). The removal percentage was modeled based on linear, interaction and quadratic terms and the values obtained from RMSE were 0.2225, 0.24449 and 0.87773 respectively. The smallest value from the linear equation suggests that the model is the best in describing the removal percentage. Analysis of variance, ANOV A was used to evaluate the main and interaction effects of each factor and the result shown that dosage and pH are statistically significant (p < 0.05) which are 0 and 0.004 respectively.